Criminology Study Of Crime Of Fencing The Stolen Goods - Supriyono Supriyono (Jurnal Daulat Hukum, 2020)
Criminal offense is regulated in Article 480 of the Criminal Code, Article 481 and 482 of the Criminal Code. Criminal detention is an act that is prohibited by law, because detention is obtained from crime. Criminology perspective plays an important role in studying fencing acts as a form of criminal action by looking at the elements inherent in criminal acts of detention. The formulation of the problem in this research is how Criminology review in the criminal act of holding stolen goods? In this study the authors used a normative juridical method with research specifications in the form of descriptive analysis. The data used for this research are primary and secondary data taken by field observation, interviews, and literature study. Based on the research, it can be concluded that the criminology point of view shows legal efforts for the crime in the form of composing legislation (criminalization process) in the form of legal products in the laws governing criminal offenses stipulated in Criminal Code Article 480-482, in the scope of criminology as criminal etiology in criminal offenses namely internal and external factors.Keywords: Criminology; Criminal Offense; Stolen Goods.